2022
DOI: 10.3390/genes13122325
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigation of Chemotherapeutic Resistance and miRNA Expressions in Head and Neck Cancers: A Thorough PRISMA Compliant Systematic Review and Comprehensive Meta-Analysis

Abstract: Chemoresistance is a significant barrier to combating head and neck cancer, and decoding this resistance can widen the therapeutic application of such chemotherapeutic drugs. This systematic review and meta-analysis explores the influence of microRNA (miRNA) expressions on chemoresistance in head and neck cancers (HNC). The objective is to evaluate the theragnostic effects of microRNA expressions on chemoresistance in HNC patients and investigate the utility of miRNAs as biomarkers and avenues for new therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…These results confirmed the upregulation of miR-145 among this chemosensitive cell line previously reported by this group [47]. This supports other research that demonstrates that the downregulation of miR-145 expression was associated with oral cancer diagnosis and progression, while miR-145 upregulation correlated with improved prognosis and increased survival [31,39].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results confirmed the upregulation of miR-145 among this chemosensitive cell line previously reported by this group [47]. This supports other research that demonstrates that the downregulation of miR-145 expression was associated with oral cancer diagnosis and progression, while miR-145 upregulation correlated with improved prognosis and increased survival [31,39].…”
Section: Discussionsupporting
confidence: 91%
“…More specifically, systematic reviews and meta-analyses have established microRNA expression profiles for oral cancers including miR-21, miR-31, miR-155, and miR-196 [35][36][37][38]. In addition, many studies have revealed that microRNA expression also functions to mediate chemotherapy resistance among oral cancers [24,39]. For example, increased tumor resistance to Cisplatin has been linked with the upregulation of miR-21, but resistance among oral cancer has also been linked with miR-24, miR-218, and miR-629 upregulation, while miR-15b, miR-27b, and miR-155 upregulation may be associated with decreased resistance to Cisplatin within these same tumors [40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…However, this treatment may also be combined with radiation or chemotherapy to eliminate other potential cancerous cells that may not have been removed through surgical resection [ 9 , 10 ]. New evidence suggests that radiation and chemotherapy resistance are growing concerns within the field of oral oncology treatment, and more research is focused on determining the mechanisms that mediate these phenomena [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%